2022
DOI: 10.1186/s13690-022-00827-0
|View full text |Cite
|
Sign up to set email alerts
|

Trust and willingness towards COVID-19 vaccine uptake: a mixed-method study in Ghana, 2021

Abstract: Background On the account of limited doses of COVID-19 available to the country, the Government of Ghana created a priority list of persons to target for its vaccination agenda. In this paper, we look at trust and how it informs willingness to take the COVID-19 vaccine among persons targeted for the first phase of COVID-19 vaccination program in Ghana. Methods A sequential mixed-method investigation was conducted among the priority population - per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
33
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 62 publications
8
33
3
Order By: Relevance
“…This indicates that males are more likely to have nightmares, intrusive thoughts, or emotion-laden images related to COVID-19 due to either direct or vicarious traumatic exposure to COVID-19 and using maladaptive responses such as compulsive checking and reassurance seeking [73], which may exacerbate their COVID-19 stress levels. The current findings are consistent with previous studies that reported sex differences in COVID-19 attitudes and behaviours [63,64], leading to sex differences in COVID-19 infection [65], although other studies revealed contradictory findings on COVID-19 vaccine acceptance [61,66]. In sum, this study affirms that there are sex differences and that female adolescents are more likely to perceive COVID-19 as a dangerous health problem and be more prepared to comply with the available scientific preventive protocols, which may enhance the effectiveness of dealing with the pandemic.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This indicates that males are more likely to have nightmares, intrusive thoughts, or emotion-laden images related to COVID-19 due to either direct or vicarious traumatic exposure to COVID-19 and using maladaptive responses such as compulsive checking and reassurance seeking [73], which may exacerbate their COVID-19 stress levels. The current findings are consistent with previous studies that reported sex differences in COVID-19 attitudes and behaviours [63,64], leading to sex differences in COVID-19 infection [65], although other studies revealed contradictory findings on COVID-19 vaccine acceptance [61,66]. In sum, this study affirms that there are sex differences and that female adolescents are more likely to perceive COVID-19 as a dangerous health problem and be more prepared to comply with the available scientific preventive protocols, which may enhance the effectiveness of dealing with the pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…Measurement scales have been developed to assess COVID-19 vaccination acceptance [49][50][51][52], which have helped researchers to objectively examine COVID-19 vaccination acceptance in various countries. Factors influencing COVID-19 vaccinations seem to be wide and varied, from external factors such as the culture, political governance, gross domestic product, and inter-country relationships [53][54][55][56][57][58][59][60][61] to internal or personal factors such as age, sex, educational levels, profession, and lifestyle behaviours [53,54,[56][57][58]61,62]. For instance, previous studies have reported sex differences in COVID-19 attitudes and behaviours [63,64], leading to sex differences in COVID-19 infection [65], although other studies revealed contradictory findings on COVID-19 vaccine acceptance [61,66,67].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S1: Strobe Statement for the study, Table S2: Studies conducted on the general population of other LMICs testing vaccine acceptance and related factors. References [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…The Talkwalker posts and interactions are mainly published by men and young adults, excluding the voices of women, youth, and older people. In addition, here are still significant numbers of people, particularly in vulnerable populations such as low-income individuals and those who cannot read and write, who are not reached by digital platforms [ 44 ]. Accordingly, there is a need to merge offline listening systems with the infodemic management system, such as the perspectives of community leaders, who are highly respected in Ghana, and women, who play a key role in the vaccination decision-making of their children in Ghana [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%